Oral presentation errors of Malaysian students in an English for Academic Purposes (EAP) Course - Muhamad, Ainon Jariah; Ahamad Shah, Mohamed Ismail; Engku Ibrahim, Engku Haliza; Sarudin, Isarji; Abdul Malik, Faridah; Abdul Ghani, Rozina (IDOSI Publications, 2013)
This study investigates the errors English for Academic Purposes (EAP) students made in their oral presentations. An understanding of the types of errors made by students in EAP will enable language educators to assist students in improving their oral proficiency. The errors in oral presentations of 32 students were investigated using [1] surface structure taxonomy, which specifies four main ways by which students modify the target forms, namely, misformation, misordering, addition and omission. Findings indicate that misformation accounted for the majority of the total grammatical errors identified followed by omission and addition. In addition, verb form, word form and article were found to be the three most frequent types of errors made by the students.